Multi-Site Tumour Sampling Improves the Detection of Intra-Tumour Heterogeneity in Oral and Oropharyngeal Squamous Cell Carcinoma - Jie, Weiping; Bai, Jiaying; Yan, Jing; Chi, Yanting; Li, Bin-bin (Frontiers in Medicine, 2021)
Background: Oral squamous cell carcinoma (OSCC) and oropharyngeal squamous cell carcinoma (OPSCC) are very common in head and neck malignancy. Intratumour heterogeneity (ITH) may hamper their responses to treatment. Hence, novel tumour sampling methods that reflect ITH are required. In this study, we investigated the clinical significance of multi-site tumour sampling (MSTS) to detect ITH in OSCC and OPSCC. Methods: One hundred eighty-two paired specimens were sampled by routine sampling (RS) or MSTS, respectively. Histologically, tumour grade, peri-tumoural vascular and lymphatic growth, perineural permeation, tumour necrosis, and muscle invasion were assessed. Immunohistochemically, the positive and average detection rates of P53(mutant), ki67 and CyclinD1 were detected. The exon 9 and exon 20 mutations of PIK3CA gene and the methylation status of the CDKN2A promoter were analysed. Results: Microscopically, the detection rate of perineural permeation, the detection density of peri-tumoural vascular and lymphatic growth, necrosis and muscle invasion in MSTS were significantly more frequent than those in RP (P < 0.05, P < 0.05, P < 0.01, P < 0.01). MSTS resulted in a higher detection rate of P53 (mutant), ki67, and CyclinD1 expression than did RS, but the difference was not significant. MSTS's detection rates in PIK3CA gene mutation and gene methylation sequencing in CDKN2A gene promoter region were both higher than RP (P < 0.05, P < 0.01). To be emphasised, the hotspot mutation H1047Rwas detected in one MSTS specimen (case 24M5) but in no RS specimens. Conclusions: This study verified that MSTS's advantage in the reflection of morphological and molecular characteristics of OSCC and OPSCC. MSTS was more representative than RP. Therefore, MSTS can compensate the RP limitations in ITH detection especially in large tumours.